PENGUNGKAPAN MODALITAS CAN DAN COULD PADA PENERJEMAHAN BAHASA INGGRIS KE DALAM BAHASA INDONESIA - R. Renny Soelistiyowati (Ranah: Jurnal Kajian Bahasa, 2016)
This paper is aimed to disclose the modality elements of English that are translated into Indonesia language based on the meaning derived from its context, such as the difference between the units and part of speech; the equivalence of the modality elements of primary modifier verb can and secondary modifier verb could translated from English to Indonesian language, and also the probability of the translation of primary modifier verb can and secondary modifier verb could translated from English to Indonesian language. The source of the data is The Naked Face novel and its translation version, Muka Telanjang. It was found that 54 sentences contain can and could. It was also found 57 modifier verbs can and could that consist of 18 primary modifier verbs can and 39 modifier verbs could. In addition, there were also units shifting from (could) to phrase (bisa saja), part of speech shifting such as modifier verb (I can’t) into adjective (tidak pandai), equivalence from (can) and (could) into some vocabularies of Indonesian language and also translation equivalence probability of modality can and could into some vocabularies in Indonesian language with their respective frequencies. ABSTRAKPenyusunan makalah ini bertujuan untuk mengungkapkan unsur modalitas bahasa Inggris yang diterjemahkan ke dalam bahasa Indonesia berdasarkan makna yang diperoleh dari konteksnya. Misalnya, perbedaan unit dan kelas kata; kesepadanan unsur modalitas verba pewatas primer can dan verba pewatas sekunder could yang diterjemahkan dari bahasa Inggris ke dalam bahasa Indonesia; serta probabilitas penerjemahan unsur modalitas bahasa Inggris verba perwatas primer can serta verba pewatas sekunder could yang diterjemahkan ke dalam bahasa Indonesia. Sumber data dalam makalah ini diambil dari novel The Naked Faced serta terjemahannya Muka Telanjang. Dari proses penelitian yang dilakukan, ditemukan 54 kalimat yang mengandung modalitas can dan could. Ditemukan pula 57 verba pewatas pewatas can dan could yang terdiri dari 18 verba pewatas primer can dan 39 verba pewatas sekunder could. Selain itu, terdapat pergeseran unit seperti dari kata (could) menjadi frasa (bisa saja) serta terdapat pergeseran kelas kata, seperti dari verba pewatas (I can’t) menjadi adjektiva (tidak pandai); terdapat kesepadanan dari (can) dan (could) ke dalam beberapa kosakata bahasa Indonesia; serta terdapat probabillitas kesepadanan penerjemahan modalitas can dan could menjadi beberapa kosakata bahasa Indonesia dengan frekuensinya masing-masing.